Some Considerations about the Relationship between Science and Philosophy in Ptolemaic Writings: An Analysis from Its Teleological Model of Explanation - Gargiulo, María Teresa (Revista Archai, 2018)
There is abundant bibliography today that has been concerned with presenting the astronomer as an empiricist scientist focused on the task of saving appearances and disconnected from all kinds of theological or metaphysical reflection. In opposition to this line of reading, we will limit ourselves to study in his Almagest and in his Harmonics the scientific-mythological unit that crosses both its normative image of science and its own scientific practice. This unity, in our view, allows us to understand Ptolemy’s notion of science from more comprehensive coordinates than empiricism offers.